Aktivitas Antiinflamasi Ekstrak Etanol Echinometra mathaei pada Tikus Putih Jantan dengan Induksi Karaginan - Angelica Kresnamurti; Hardiyono Hardiyono; Febriana Siswulandari; Iwan Sahrial Hamid (Pharmacon: Jurnal Farmasi Indonesia, 2021)
Sea urchin (Echinometra mathaei) is one of the marine biota that contains high flavonoid and phenolic compounds that are potent as anti-inflammatory and antioxidant. This study aimed to measure the anti-inflammatory activity of the 70% ethanol extract of sea urchins in male white rats induced by carrageenan. Anti-inflammatory activity test using 5 groups of rats selected randomly, each group consists of 5 rats. Negative control group, positive control group, and 3 groups of extracts (doses of 100, 200, and 400mg/kgBW). Each group was induced using 1% carrageenan subplantarly and the volume of edema was measured using a mercury plethysmometer every 30 minutes for 3 hours. The data were statistically analyzed using one-way Anova. The results showed that the percentage of inflammatory inhibition in the positive control group, and the Echinometra mathaei ethanol extract group (dose of 100, 200, and 400 mg/KgBW) showed a significant difference (P0.05) with the negative control group with a percentage value of Inflammation inhibition was 61.11%, 85.19%, 85.19%, and 74.07%, respectively. The administration of sea urchin ethanol extract at all doses had a higher percentage of anti-inflammatory than diclofenac sodium, but increasing the extract dose did not significant increase inflammatory inhibition. This research concluded that 70% ethanol extract of Echinometra mathaei at doses of 100, 200, 400 mg/KgBW has strong anti-inflammatory activity potential.